Endometrial Polyps: Update Overview on Etiology, Diagnosis, Natural History and Treatment - Mariana De Cunha Vieira; Amerigo Vitagliano; Mariana Costa Rossette; Luiz Cavalcanti de Albuquerque Neto; Alessandra Gallo; Attilio Di Spiezio Sardo (IMR Press, 2022)
Objectives: To provide an updated literature overview about the pathophysiology, natural history, diagnosis and treatment of endometrial polyps (EPs). Findings in Brief: EPs are focal, sessile or pedunculated projections of endometrial lining, resulting from the hyperplastic overgrowths of endometrial glands and stroma around a vascular core. These are the most common intrauterine diseases, affecting up to 34.9% of the women during their lifetime. EPs may vary in size, location, histopathology, natural history and clinical presentation. Importantly, EPs are common in women suffering with infertility (i.e., up to 32% in patients undergoing in-vitro-fertilization) and are not exempt from risk of malignant transformation (occurring in about 3.1% of patients). For these reasons, EPs represent one of the most significant gynaecological problems worldwide. Trans-vaginal ultrasound has fair diagnostic accuracy for EPs, with sensitivity and specificity of 91% and 90%, respectively. Nevertheless, the current gold standard for EPs diagnosis is hysteroscopy, which allows a direct visualization of EPs size and morphology. Moreover, this technique enables safe EPs excision, with a low risk of incomplete tissue removal (about 1.9% and 4.3% in inpatient and outpatient settings, respectively), and variable recurrence rate based on individual risk factors (ranging between 2.5% and 43.6%). Besides hysteroscopy, other management options for EPs can be considered on a case by case basis. Conclusions: Our review may be helpful for updating clinicians' knowledge on the management of EPs.